The relationship between self-esteem and diabetes distress in type 2 diabetes mellitus patients at pahandut community health center Palangka Raya City - Febertha Atuh, Christine; Datak, Gad; Utama, Nang Randu; Sylvia, Ester Inung (Journal of Midwifery and Nursing, 2024)
Diabetes Mellitus is a non-communicable metabolic disease characterized by an increase in blood sugar levels >200 mg/dl due to impaired secretion of insulin. Manifestations of Diabetes Mellitus are polyphagia, poldipsi, polyuria and drastic weight loss. This research aims to determine the relationship between Self-Esteem and Diabetes Distress in Type 2 Diabetes Mellitus Patients at the Pahandut Community Health Center, Palangka Raya City. The research design is quantitative with a cross-sectional approach, the number of samples used was 41 respondents using a purposive sampling technique. The data collected in this study is demographic data including age, gender, highest level of education, occupation, income, length of time suffering from DM, visits to health services, Self-Esteem, Diabetes Distress and questionnaires. The results of the study showed that there was a relationship between self-esteem and Diabetes Distress in Type 2 Diabetes Mellitus  Patients at the Pahandut Health Center, Palangka Raya City (p=0.036).